Personal Characteristics and Intention for Entrepreneurship - Murat Yalcintas; Oykü Iyigun; Gokhan Karabulut (Global Labor Organization (GLO), 2021)
This study analyzes the relationship between entrepreneurship intention and personal characteristics and skills by using the surveys we conducted in Turkey on 1465 senior university students. We use a modified version of the Entrepreneurial Orientation (EO) scale and the Political Skills Inventory to measure some personal characteristics and skills. We also use the nine sub-dimensions of these two scales. Probit model and wavelet coherence analysis results show that proactivity, entrepreneurship, and networking sub-dimensions of the scales are related to entrepreneurship intention. We also find that gender, the number of siblings, the grade point average (GPA) of the students, their family's education level, the parent' ownership of an enterprise, and the number of non-governmental organizations (NGO) that they are a member of are also related to entrepreneurship intention. Results may be useful to understand and enhance entrepreneurship potential.
Keywords: C90; D63; 330; Entrepreneurship; Self-employment entry; Occupational choice